The Effect of the Contextual Teaching and Learning (CTL) Model on Reading Comprehension Skills in Indonesian Language Subjects at UPT SD Negeri 10 Pulau Punjung - Antik Estika Hader; Rusdi Indra Hasibuan; Putri Regina Prayoga (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research is motivated by the lack of reading comprehension skills in Indonesian Language subjects at UPT SD Negeri 10 Pulau Punjung. Efforts to overcome this problem are by implementing the Contextual Teaching and Learning (CTL) learning model. This study aims to determine the Effect of the Contextual Teaching and Learning (CTL) Learning Model on Reading Comprehension Skills in Indonesian Language Subjects at UPT SD Negeri 10 Pulau Punjung. This type of research uses a quantitative model, with a Two Group Pretest-Posttest Design approach. The population in this study were all students in grades IVa & IVb at UPT SD Negeri 10 Pulau Punjung. The sample of this study was 19 students in grade IVa and 19 students in grade IVb. The data collection technique in this study was a test in the form of essay and objective questions. The data analysis technique used was the normality test, homogeneity and hypothesis testing, namely the t-test. Based on the hypothesis test, the results obtained were 0.015 < 0.05, it can be concluded that there is an influence of the application of the Contextual Teaching and Learning (CTL) learning model on the Ability to Read Comprehension in Indonesian Language Subjects at UPT SD Negeri 10 Pulau Punjung. So it can be concluded that based on this research, the application of the Contextual Teaching and Learning (CTL) learning model has a good influence on students' Reading Comprehension Ability in Indonesian Language Subjects at UPT SD Negeri 10 Pulau Punjung.